Tech for Kids untuk Memperkenalkan Siswa Mengenai Tahapan Merakit Purwarupa dalam Proses Desain Rekayasa - Deny Nusyirwan; Eko Prayetno; Sapta Nugraha; Harits Aditya Nugraha; Lilis Agustina Sinaga; Allysia Shafira; Muhammad Abyan Fadillah (Universitas Mathla'ul Anwar Banten, 2021)
TECH FOR KIDS FOR INTRODUCING THE STUDENTS ABOUT THE STAGE OF PROTOTYPE ASSEMBLING IN ENGINEERING DESIGN PROCESS. Individuals must be able to adapt effectively to changing situations rather than rely solely on rote learning procedures. Therefore, the call for 21st century skills is a call for deeper learning - helping students to develop transferable knowledge that can be applied to new situations and problems. Virtual prototypes are perhaps the greatest benefit that comes from using computer-aided designs. Virtual prototypes allow high-quality design. Adjust spare parts with proper clearance and check for parts glitches before spending on material shopping. Designers can also